Reduced Mass Flux due to Mixing in Controlled Exchange Flows with Possible Applications to The Indonesian Through-Flow - Prastowo, Tjipto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2008)
The Indonesian Through-Flow (ITF) is a system of surface ocean currents flowing from the western Pacific Ocean through numerous straits and sills within the eastern Indonesian seas into the Indian Ocean. The ITF carries a large amount of heat and water affecting climate on regional and global scales. A more detailed, comprehensive study by either direct measurements, numerical simulations or laboratory experiments is then needed to fully understand the flow. In this context, laboratory experiments are used to study the characteristics of mixing in density-driven exchange flows, so as to examine similar situations occurring in the flow. Theexperiments have also particular relevance to improving predictions of mixing in deep overflows, as well as to understanding the dynamics of exchange flows between water bodies such as estuaries, marginal seas and the open ocean. Vigorous turbulence which leads to irreversible mixing is observed in the experiments and the resulting reduction in exchange flux is measured to be 82% of the maximal exchange predicted by hydraulic theory. The possible application of the experimental results to Indonesian sea settings is also discussed as the results are relevant to physical oceanographic problems in the Indonesian waters.